AKSONOMETRIK PROYEKSIYALARNI O‘QITISHDA SIFAT VA SAMARADORLIKKA ERISHISH OMILLARI - Valiyev, A.N.; Mardov, S.; Esboganova, B.D. (SCIENCE and SOCIETY, 2016)
The article deals with the study of means of developing students’ space imagination on the example of the theme of acsonometric projection.